2007
DOI: 10.1021/jo062380y
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Understanding of the Reaction of Bis(bromomethyl)quinoxaline 1-N-Oxides with Amines Using Substituent Effects

Abstract: The reaction of bis(bromomethyl)quinoxaline N-oxides with amines is interesting from a reaction mechanism perspective and due to the reported biological activity of compounds in this general class. The complex mechanism of this reaction (particularly in the case of primary amines) is complicated further when C6 or C7 substituted mono-N-oxides are considered. In this study, the synthesis and subsequent characterization of a series of 2,3-bis(bromomethyl)quinoxaline 1-N-oxides is reported. Experimental and compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
8
1
Order By: Relevance
“…Studies with model substrates have shown that 1 can react with both thiols and amines21 (see also below). To determine whether the biotinylated proteins in the parasite extract had reacted with 2 through a thiol(s) or an alternative protein nucleophile(s), duplicate parasite samples were extracted either in the presence or absence of iodoacetamide prior to incubation with 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies with model substrates have shown that 1 can react with both thiols and amines21 (see also below). To determine whether the biotinylated proteins in the parasite extract had reacted with 2 through a thiol(s) or an alternative protein nucleophile(s), duplicate parasite samples were extracted either in the presence or absence of iodoacetamide prior to incubation with 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[8,9] Subsequent condensation of 4 with 1,2-phenylenediamine gave high yields of the mono-bromo quinoxaline 5 that was oxidised (mCPBA, 2 equiv) to give 2. The use of limited amounts of mCPBA led to a mixture of the two mono-Noxides 6 and 7, [10] as it was thought that pure samples of these two analogues would enable the role of the N-oxide functional groups to be explored.…”
mentioning
confidence: 99%
“…The synthesis of the latter was envisioned by the Suzuki-Miyaura reaction of bromo-1H-benzo[d]imidazol-2(3H)-one (10) with boronate (12) [22]. Preparation of 10 was commenced by the basic hydrolysis of acetamide (7) to produce nitroaniline (8), which in turn was transformed to benzenediamine (9) by the action of stannous chloride 26 . Reaction of 9 with CDI finally produced 10 in 62% yield.…”
Section: Resultsmentioning
confidence: 99%